Integration of cyber defense and conventional security in addressing non-military threats in the digital era - Fitria, Rosi; Supriyadi, Asep Adang (Journal of National Paradigm-Based Resilience Strategy, 2025)
Background: The development of digital technology has transformed the landscape of threats to national security, with non-military threats, including cyberattacks, digital terrorism, and disinformation, becoming increasingly urgent. These threats have the potential to undermine social, economic, and political stability. This study aims to analyze the integration of cyber and conventional defense in strengthening national resilience against non-military threats. Method: This research employs a qualitative approach, analyzing literature and policies of national security institutions regarding non-military threats. Primary data were obtained through a literature review of journals and articles accessed via SCOPUS. The study began with brainstorming to identify topics, subthemes, and relationships between concepts. Findings: The results indicate that integrating cyber and conventional defense enhances the response to hybrid threats. Joint management of cyber and physical threats, along with sharing resources and information between agencies, enhances the effectiveness of responses to complex threats. Conclusion: This study concludes that integrating cyber and conventional defense systems is crucial for addressing threats in the digital age. Its success depends on clear policies, regulations, and strict oversight to ensure effective coordination between relevant agencies. Originality/Novelty of the Article: The article's originality lies in proposing an integrated defense model that combines conventional and cyber strategies to address hybrid threats, a topic that has not been extensively discussed in the literature.